Endoscopic sphincterotomy with sphincteroplasty for the management of choledocholithiasis: a single‐centre experience. Issue 9 (17th March 2015) - Ho, Simon; Rayzan, Daniel; Fox, Adrian; Kalogeropoulos, George; Mackay, Sean; Hassen, Sayed; Banting, Simon; Cade, Richard
Abstract: Background: Balloon dilatation of the ampulla at endoscopic retrograde cholangiopancreatography (ERCP) is increasingly utilized in the management of large bile duct stones. The aim of this study was to review and compare the outcomes of using endoscopic sphincterotomy with endoscopic balloon dilatation (sphincteroplasty) in a combined approach as a single‐stage (immediate) or a two‐stage procedure (delayed). Methods: A retrospective review of medical records for all patients undergoing ERCP and balloon dilatation for choledocholithiasis between January 2010 and December 2012 was undertaken. Outcomes measured included patient demographics, stone size, degree of dilatation performed, success of stone extraction, number of procedures required for duct clearance and procedure‐related complications. Results: One hundred and thirty‐six ERCPs were performed with balloon sphincteroplasty. One hundred and four had a previous sphincterotomy with a delayed balloon dilatation and 32 had sphincterotomy with immediate dilatation. The overall clearance rate of the common bile duct for immediate and delayed groups was 93% (28/30) and 93% (81/87), respectively. Bile duct clearance after the first procedure was achieved in 70% (21/30) of patients in the immediate group and 74% (64/87) in the delayed group. There were six complications in the delayed group and four in the immediate group. The most frequently used balloon size was 10 mm for both groups with mean sizes of 10.34 (2.93) and 11.73 (2.87) in the immediate and delayed groups, respectively. Conclusion: Our study suggests that use of a combined approach is safe and effective and may provide benefits over using endoscopic balloon dilatation or endoscopic sphincterotomy alone in the treatment of choledocholithiasis.